The Authority Of The National Land Agency And The Legal Certainty Of Land in Indonesia - Syukur, Syukur; Maryono, Maryono; Akkapin , Suppaphorn (CV. Era Digital Nusantara, 2025)
This article discusses the authority of the National Land Agency (BPN) in creating land legal certainty in Indonesia, as well as the challenges and strategies needed to improve the effectiveness of land management and dispute resolution. Through an analysis of regulations governing BPN's authority, such as the Basic Agrarian Law and Minister of Agrarian Affairs and Spatial Planning Regulations, it is found that BPN has a vital role in land registration and dispute resolution. However, challenges such as overlapping authority, multiple certificates, and land mafia practices still hinder effective implementation. This research recommends strengthening BPN's authority through the establishment of a clearer and more specific law and the addition of an article on Land Civil Servant Investigators (PPNS) in Law No. 5/1960. Hopefully, these measures can strengthen land law enforcement, improve transparency and accountability, and create better legal certainty for the community. Thus, BPN can contribute more effectively in managing and resolving land disputes, as well as promoting justice in natural resource management in Indonesia.